Aplikasi Pengenalan Organisasi Muhammadiyah Berbasis Android Menggunakan Metode Linear Congruent Generator - Muntahanah Muntahanah; Joka Jasri (Jurnal Media Computer Science, 2024)
Misconceptions about Islamic teachings that are understood by some Indonesian Muslims are the result of an unfinished adaptation between Islam and the local traditions of the archipelago, which initially contained animism and dynamism. So that in practice Muslims in Indonesia show things that are contrary to the principles of Islamic teachings, especially those related to the principles of the Islamic creed which reject all forms of polytheism, taqlid, bid'ah, and superstition. To introduce Muhammadiyah teachings requires the help of technology that is currently developing. By using android, we can introduce Muhammadiyah to more people because it can be used anywhere and anytime. The application will display the history of the founding of Muhammadiyah, the teachings of Muhammadiyah and the practical worship of Muhammadiyah. It is hoped that this application will introduce Muhammadiyah teachings more easily with a wider reach. To attract the interest of children and adolescents in getting to know Muhammadiyah teachings, the author will add a quiz feature or question and answer practice so that there is interaction between the user and the application that is like educational games. In the quiz feature, the Linear Congruent Generator (LCG) algorithm will be implemented which functions to randomize the questions so that the questions that appear will always change. Applications for the introduction of Islam based on Android using the linear congruent generator method were successfully built using the Java programming language with Android studio software. Applications can provide discussion material about Muhammadiyah. Randomization of questions using the LCM Algorithm (Linear Congruent Method) has repetition but is easy to understand and implement into the application.